"Those who have been born of God do not sin, because God"s seed abides in them" − Soteriology in 1 John - Van der Merwe, Dirk (HTS teologiese studies, 2012)
The author of 1 John states that ‘those who have been born of God do not sin, because God’s seed abides in them’. This is found explicitly four times (3:5; 3:6 bis; 3:9; 5:18), and implicitly once (2:29). The author links these assertions to the life of Jesus (1 Jn 3:5). Anyone reading these texts is likely to find them hard to bear, because the author appears to be discussing a doctrine of Christian perfection. However, in this research I shall attempt to show (using a socio- rhetorical approach) that, in fact, these assertions should not be interpreted literally by the reader. Instead, these texts are part of the author’s rhetorical construction to designate just how radical he sees the salvation event. The author substantiates the understanding and meaning of these radical assertions in his depiction of Christian existence as existence in a family, the familia Dei.